Ichthyosis prematurity syndrome caused by a novel missense mutation in FATP4 gene‐a case report from India. Issue 1 (1st December 2015) - George, Renu; Santhanam, Sridhar; Samuel, Rekha; Chapla, Aaron; Hilmarsen, Hilde Tveitan; Braathen, Geir Julius; Reinholt, Finn P.; Jahnsen, Frode; Khnykin, Denis
Key Clinical Message: Ichthyosis prematurity syndrome (IPS) is reported mainly from Scandinavia where most of the cases are homozygous or compound heterozygous for the nonsense mutation c.504C>A (p.Cys168*) in exon3 indicating a common ancestor for this mutation. The occurrence of IPS in an Indian patient suggests that it is more widespread than previously reported. Abstract : Ichthyosis prematurity syndrome is reported mainly from Scandinavia where most of the cases are homozygous or compound heterozygous for the nonsense mutation c.504C>A (p.Cys168*) in exon3 indicating a common ancestor for this mutation. The occurrence of IPS in an Indian patient suggests that it is more widespread than previously reported.